PENERAPAN METODE DISKUSI DALAM MENINGKATKAN KEMAMPUAN GURU MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR DI SD NEGERI 007 KOTA LAMA KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Suhartatik (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
From preliminary observations conducted at SD Negeri 007 Kota Lama, it was found that teachers utilized the school environment as a learning resource only two to three times per semester. Teachers tended to conduct learning activities inside the classroom even though the learning materials were closely related to the school environment. Interviews with teachers revealed that most of them were reluctant to take students outside the classroom due to difficulties in supervision, while some teachers admitted that they lacked the knowledge and skills to utilize the school environment as a learning resource. Based on these problems, school action research was conducted with the aim of improving teachers’ ability to utilize the school environment as a learning resource and identifying their strengths and weaknesses as a basis for improvement. This study was designed as school action research conducted in two cycles, with 18 classroom teachers at SD Negeri 007 Kota Lama as the research subjects. The results showed an improvement in teachers’ ability to utilize the school environment as a learning resource through a discussion-based approach. By optimizing discussions within the Teacher Working Group (KKG), teachers were able to address problems related to the use of the school environment in the teaching and learning process. Overall, there was a noticeable increase in teachers’ abilities, particularly in the category of good performance. Based on the research indicators, teachers’ abilities in the second cycle reached 81.8% in the good category, exceeding the predetermined success criterion of 70%.